The Trueness between Conventional Impression and Different Intraoral Scanners for All-on-4 Implants: An In vitro Comparative Study - Alsulimani, Osamah A.; Alhaddad, Abdulrahman J.; Abuzinadah, Samar H.; Alzahrani, Saeed J.; Alghamdi, Hamed S.; Ghander, Farah A.; Magadmi, Refad M. (European Journal of Dentistry, 2025)
To assess and compare the trueness (dimensional discrepancy and degree of deviation) of various methods of impressions for All-on-4 implants.This investigation employed a single-piece artificial mandibular jaw with four implants arranged in an All-on-4 configuration. Three impression methods were compared: one open-tray conventional impression digitized after pouring, and two intraoral scanners, TRIOS 5 and Runyes 3DS 3.0. A reference scan (control) was conducted with a laboratory-based scanner. All scans were performed using scan bodies and exported as Standard Tessellation Language (STL) files. A total of 30 STL scans were produced (n = 10). The dimensional discrepancy (along the X, Y, and Z axes) and the overall degree of deviation in the position were assessed. Data analysis was conducted using Brown–Forsythe one-way analysis of variance and Tamhane's post hoc tests (p < 0.05).The mean degree of deviation for scan bodies was as follows: TRIOS 5 (1.11 ± 0.06 mm), Runyes 3DS (1.02 ± 0.05 mm), and conventional (0.82 ± 0.16 mm). Statistically significant differences were found among all impression methods (p < 0.05). While the conventional method showed the highest trueness, it had the greatest standard deviation (SD, 0.16), which was the least consistent among them. The Runyes 3DS scans displayed the highest precision with the degree of deviation of 0.05 (± SD). Dimensional discrepancies mainly occur on the Z-axis across all three impression methods. Conventional impressions showed statistically significant discrepancies in the Y- and Z-axes, while TRIOS 5 images had statistically significant discrepancies in the X- and Z-axes. Runyes 3DS readings were statistically significantly discrepant in the Z-axis.While both conventional methods and digital scans have their merits, traditional impression methods may offer improved trueness in full-arch implant cases. Utilizing the open-tray system with suitable materials and methods can enhance precision and lead to more reliable outcomes.
Keywords: degree of deviation; All-on-4; trueness; intraoral scan; precision; accuracy